IMPLEMENTASI DYNAMIC PROGRAMMING PADA PENENTUAN JENIS MATERIAL UTAMA BANGUNAN ARENA FUTSAL - Andree Anthony; R. Gunawan Santosa; Yuan Lukito (Universitas Kristen Duta Wacana, 2015)
Building futsal court need some planning, especially about the materials needed to build a futsal court such as synthetic grass, roofs, walls, benches, and some other materials. Each of materials have many choices usually based on quality and price. Thus it needs a system to assist on calculating the optimum materials combination based on a specified budget. Minimax Route method are used with dynamic programming techniques to maximize the quality of materials while minimizing the price of materials chosen. Based on system testing conducted to futsal court owners in Yogyakarta, the implementation are helpful and have many useful information for someone who want to build futsal court.